A Novel Missense Variant of TP63 Heterozygously Present in Split-Hand/Foot Malformation. (26th November 2020) - Geng, Hao; Tang, Dongdong; Xu, Chuan; He, Xiaojin; Zhang, Zhiguo
Abstract : Background . Split-hand/foot malformation (SHFM) is a severe congenital disability mainly characterized by the absence or hypoplasia of the central ray of the hand/foot. To date, several candidate genes associated with SHFM have been identified, including TP63, DLX5, DLX6, FGFR1, and WNT10B . Herein, we report a novel variant of TP63 heterozygously present in affected members of a family with SHFM. Methods . This study investigated a Chinese family, in which the proband and his son suffered from SHFM. The peripheral blood sample of the proband was used to perform whole-exome sequencing (WES) to explore the possible genetic causes of this disease. Postsequencing bioinformatic analyses and Sanger sequencing were conducted to verify the identified variants and parental origins on all family members in the pedigree. Results . By postsequencing bioinformatic analyses and Sanger sequencing, we identified a novel missense variant (NM_003722.4:c.948G>A; p.Met316Ile) of TP63 in this family that results in a substitution of methionine with isoleucine, which is probably associated with the occurrence of SHFM. Conclusion . A novel missense variant (NM_003722.4:c.948G>A; p.Met316Ile) of TP63 in SHFM was thus identified, which may enlarge the spectrum of known TP63 variants and also provide new approaches for genetic counselling of families with SHFM.